Scrutinization of FOCDMA Code Families for Application in Optical Communication - C.S. Mishra; M. Ravikumar (Institute of Advanced Engineering and Science, 2017)
In code division multiple access (CDMA) code construction and analysis, the bit error rate due to multiple access interference is an important performance parameter which is overcome to some extent by generating almost orthogonal codes. Ideal orthogonal code families should have zero autocorrelation and no crosscorrelation. The building of fiber-optic CDMA (FOCDMA) is based on binary, unipolar spreading codes, which in turn requires considerably longer length of spreading codes in order to satisfy these constraints. Spreading an optical bit in wavelength, time and multiple fibers is observed to satisfy the constraints for accommodating sufficiently large number of users with a comparatively smaller spreading code length. Various optical code families of different dimensions have been proposed for FOCDMA. The performance of the code families varies under different conditions. In this research, some aspects of the performance issues have been considered.